The Lady and the President : The Letters of Dorothea Dix and Millard Fillmore - Snyder, Charles McCool (Book collections on Project MUSE., 1975)
When the private papers of Millard Fillmore, thought to have been destroyed in 1889, were discovered they proved to include a large number of letters to Fillmore from Dorothea Dix, the renowned crusader for the humane treatment of the insane. Almost simultaneously, the letters of Fillmore to Dix, which had lain forgotten in a private collection since 1887, became available. Thus overnight a correspondence of more than a hundred and fifty letters, spanning nearly twenty years, opened new perspectives upon two prominent Americans whose friendship was known to few during their lifetimes and had lo.